2017
DOI: 10.1080/17446651.2018.1416290
|View full text |Cite
|
Sign up to set email alerts
|

Exercise-induced myokines: a brief review of controversial issues of this decade

Abstract: Myokines, known to mediate metabolism, inflammation, and other pathophysiological conditions, have been widely investigated, including myokines induced by exercise. However, among published literature, there is substantial inconsistency in the quantification of exercise-induced myokines. Here, we summarized and compared published data regarding the effects of exercise on commonly studied myokines including apelin, Brain-derived neurotrophic factor (BDNF), Interleukin-15 (IL-15), irisin, and Secreted protein ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 67 publications
1
23
0
2
Order By: Relevance
“…Consistently, irisin levels increased after 2 weeks of exercising in our cohort of young women. Based on this and a previous study, exercise induces the secretion of myokines, like irisin, and also FGF2 15,24 . We confirmed that irisin levels were significantly different between exercise workloads.…”
Section: Discussionsupporting
confidence: 56%
“…Consistently, irisin levels increased after 2 weeks of exercising in our cohort of young women. Based on this and a previous study, exercise induces the secretion of myokines, like irisin, and also FGF2 15,24 . We confirmed that irisin levels were significantly different between exercise workloads.…”
Section: Discussionsupporting
confidence: 56%
“…Despite these positive reports of exercise in enhancing UCP1 expression (26), PRDM16 expression (24), and mitochondrial biogenesis (25), there were also reports showing that exercise does not affect thermogenic and mitochondrial activity of BAT (27) or even down-regulated the BAT thermogenesis (28). These inconsistent reports could be due to the difference in exercise types, intensity and duration, and animal physiological conditions (29), as well as the timing of sample collection following exercise (29). Up to now, the impacts of exercise during pregnancy on fetal development have only been examined in obese mothers (13), and its effects on fetal BAT development and long-term thermogenesis of offspring born to healthy mothers are unknown.…”
Section: Discussionmentioning
confidence: 99%
“…For muscle to produce these effects it produces a variety of myokines that have a direct effect on the brain (16). Among these myokines the ones that have been shown to have effects on the central nervous system include insulin-growth factor-1, brain derived nerve growth factor, cathepsin-B, fibroblast growth factor-1 and irisin (17). Irisin has been considered a major peptide communicator (18), but recently studies have suggested that the assays that have been used are very nonspecific (19,20).…”
Section: From Muscle To Brainmentioning
confidence: 99%